2013
DOI: 10.1105/tpc.113.114835
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Complex1 Expression Level Titrates Plant Growth and Abscisic Acid Sensitivity in Arabidopsis      

Abstract: Histone deacetylation regulates gene expression during plant stress responses and is therefore an interesting target for epigenetic manipulation of stress sensitivity in plants. Unfortunately, overexpression of the core enzymes (histone deacetylases [HDACs]) has either been ineffective or has caused pleiotropic morphological abnormalities. In yeast and mammals, HDACs operate within multiprotein complexes. Searching for putative components of plant HDAC complexes, we identified a gene with partial homology to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
127
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 57 publications
7
127
0
Order By: Relevance
“…Histone acetylation has been demonstrated to function in different plant hormones (23,(26)(27)(28)(29), and several histone deacetylases are known to be involved in the regulation of gene expression (30)(31)(32)(33)(34)(35)(36)(37). The data presented here showed that the C-terminal domain of EIN2 (EIN2-C) is the key factor that drives alterations in histone acetylation during the ethylene response.…”
Section: Discussionmentioning
confidence: 65%
“…Histone acetylation has been demonstrated to function in different plant hormones (23,(26)(27)(28)(29), and several histone deacetylases are known to be involved in the regulation of gene expression (30)(31)(32)(33)(34)(35)(36)(37). The data presented here showed that the C-terminal domain of EIN2 (EIN2-C) is the key factor that drives alterations in histone acetylation during the ethylene response.…”
Section: Discussionmentioning
confidence: 65%
“…In yeast, RPD3, the ortholog of Arabidopsis HDA6, has been shown to be part of a large protein complex that includes transcriptional repressors such as Switch Independent3 and Unscheduled Meiotic gene Expression1 (Grzenda et al, 2009). And there is evidence that plant HDAs also operate in multiprotein complexes containing histone-binding proteins, corepressors, and associated proteins (Gu et al, 2011;Perrella et al, 2013;López-González et al, 2014). It is thus possible that the hda6-8 mutation in the E-R motif affects the interaction of HDA6 with the complex.…”
Section: A Highly Conserved Domain In Hda6 Is Required For Its Targetmentioning
confidence: 99%
“…Including an additionally expressed red fluorescent protein from this T-DNA, the system allows the application of a ratiometric bimolecular fluorescence complementation (rBiFC) assay, significantly enhancing the credibility of results compared with classical split-FP-based vector systems (Grefen and Blatt, 2012). This system has since been successfully employed to analyze interactions of a range of different proteins (Karnik et al, 2013bPerrella et al, 2013;Hachez et al, 2014;Lipka et al, 2014.…”
mentioning
confidence: 99%